2012
DOI: 10.20473/j.djmkg.v45.i1.p52-57
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Robusta coffee beans ointment on full thickness wound healing

Abstract: Background: Traumatic lesions, whether chemical, physical, or thermal in nature, are among the most common lesion in the mouth. Wound healing is essential for the maintenance of normal structure, function, and survival of organisms. Experiments of Robusta coffee powder on rat-induced alloxan incision wound, clinically demonstrated similar healing rate with the povidone iodine 10%. No studies that look directly the effect of coffee extract in ointment form when viewed in terms of histopathology. Robusta coffee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 16 publications
1
10
0
2
Order By: Relevance
“…22 Moreover, clorogenic and caffeic acids in Robusta coffee produce antioxidant effects in enhancing angiogenesis through increased VEGF. 23 Results of research on mice even showed that the administration of Robusta coffee at a dose of 20 mg/100 g BM (equivalent to one cup of coffee in humans) increased the number of osteoclasts on the 15th day. 24 The study reported here aimed to analyze the increased number of osteoblasts and blood capillaries in orthodontic tooth movement after the administration of Robusta coffee extract This research involved sixteen healthy, male mice (Spraque Dauwley) weighing 250-300 grams and aged between 3 and 4 months.…”
mentioning
confidence: 99%
“…22 Moreover, clorogenic and caffeic acids in Robusta coffee produce antioxidant effects in enhancing angiogenesis through increased VEGF. 23 Results of research on mice even showed that the administration of Robusta coffee at a dose of 20 mg/100 g BM (equivalent to one cup of coffee in humans) increased the number of osteoclasts on the 15th day. 24 The study reported here aimed to analyze the increased number of osteoblasts and blood capillaries in orthodontic tooth movement after the administration of Robusta coffee extract This research involved sixteen healthy, male mice (Spraque Dauwley) weighing 250-300 grams and aged between 3 and 4 months.…”
mentioning
confidence: 99%
“…In a study cited by Kenisa et al 13 when Robusta coffee powder was applied on rat-induced alloxan incision wound, it demonstrated clinically similar healing rate with medications that are commonly used in wound care, such as povidone iodine 10%. In another experiment by Kenisa et al 13 20 male guinea pigs (Caviacabaya) with full-thickness wounds were treated with Robusta coffee beans extract ointment at concentrations of 22.5%, 45%, and 90%, while the control group was given ointment base material. The animals were then harvested on the fourth day.…”
Section: Discussionmentioning
confidence: 96%
“…12 It has also been reported to facilitate wound healing. 13,14 Antibacterial activities of coffee have been demonstrated against Methicillin-Resistant Staphylococcusaureus (MRSA), Streptococcus spp. 15 and a range of gram-negative bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…The laboratory test in alloxan-induced-mice noted that Robusta coffee powders speed up the wounds closure by increasing the number of lymphocytes, plasma cells, macrophages, fibroblasts, and the blood vessels that further enhance the healing process. Study in clinical setting already conducted by some researchers and found that this wound dressing technique was effectively improve diabetic ulcer healing (Kenisa & Istiati, 2012;Susanto, Puradisastra, & Ivone, 2010). However, those studies did not clearly explain the technique wound dressing applied and its healing measurement tool used.…”
Section: Introductionmentioning
confidence: 99%